Studi Literatur Penggunaan Minyak Atsiri Di Indonesia Untuk Mengatasi Gangguan Tidur - Kambira, Pretty Falena Atmanda; Lapian, Kristin Fransiska (Riviera Publishing, 2025)
Sleep disorders are a health problem that is often experienced by various population groups, especially the elderly, infants, as well as pregnant and post-natal women. Aromatherapy with essential oils is one of the non-pharmacological approaches that is increasingly used because it is considered safer and more acceptable. Objective: This study aims to systematically review studies in Indonesia that evaluate the effectiveness of aromatherapy using essential oils on sleep quality. Method: The literature search was conducted using the Google Scholar search engine with the help of the Publish or Perish application. Keywords related to